THE ISSUE OF HUMANITY IN THE STORIES OF UTKIR KHASHIMOV - Aktamova Go’zal (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This topic explores how Utkir Hoshimov, a renowned Uzbek writer, addresses the themes of affection and humanity in his literary works. Hoshimov is known for his deep insight into the inner world of ordinary people, often portraying characters facing moral dilemmas, emotional struggles, and social challenges. His stories highlight family relationships, intergenerational conflicts, and the role of kindness, respect, and compassion in human interaction. The question focuses on how Hoshimov uses literary tools such as realistic settings, character psychology, and dialogue to reveal the human essence and emotional depth of his characters, reflecting both Uzbek traditions and universal human values.